ANALISIS OPTIMASI PENGELOLAAN PERIKANAN TANGKAP DAN STRATEGI PENGEMBANGANNYA DI TELUK LAMPUNG - Hendriwan Hendriwan; M. Fedi A. Sondita; John Haluan; Budy Wiryawan (Buletin PSP, 2008)
Sutainability of fisheries resources and prosperity of stakeholders in Lampung Bay depends on goodness of capture fisheries management in the area. The objectives of the research are to determine optimum alocation of fishing unit based on carrying capacity and determine priority of capture fisheries development startegy by eliminated conflict. Some analysis methods were aplied to this research such as linear goal programming (LGP) and analytical hierarchi process (AHP). The result show that optimum alocation for trap (sero) are 542 units (added 377 from165 units), drift gillnet 1,365 units (added 1,029 from 336 units), lift net (bagan perahu) 263 unit (added 20 from 243 units) and payang remain at its numbers. This alocation do not decrease existing alocation of fishing unit in the area so conflict can be avoided and social friendly. Priority of capture fisheries development with eliminated conflict is (a) Priority I : strategy of ideal law enforcement towards any unlawfull activities (LAW strategy); (b) Priority II: strategy of fishing ground arrangement fo each of fishing unit (F. GROUND strategy); (c) Priority III: determination of autorithies between city and province government (AUTHORITY strategy) and (d) Priority 4 : alocation of kind and numbers of fishing unit that operated in the area (strategy UNIT TKP). The strategy of law, as mention previously, guite stable towards interaction among fisherman (RK stable : 0 – 1), interaction part of PPI managers is less than 50.3% (range RK stable : 0 -